Efektivitas Pengendalian Internal, Kesesuaian Kompensasi, Moralitas Individu dan Budaya Etis Organisasi Terhadap Kecurangan Pelaporan Keuangan Dana Desa di Kabupaten Halmahera Selatan - Sumiyati S. Hi. Hasim; Rizki Wahyu Utami Ohorella; Irfan Zamzam; Nurdin Nurdin (Jesya, 2026)
The purpose of this study is to analyze the influence of Internal Control, Compensation Appropriateness, Individual Morality, and Organizational Ethical Culture on Financial Reporting Fraud of Village Funds in South Halmahera Regency. The sample in this study was obtained from 185 respondents who were village officials in East Bacan Tengah Subdistrict and South Bacan Subdistrict, South Halmahera Regency. This study used multiple linear regression analysis with the SmartPLS 4.1.1.1 analysis tool. The results of the study found that Compensation Appropriateness had an effect on Fraudulent Financial Reporting of Village Funds. Meanwhile, Internal Control, Individual Morality, and Organizational Ethical Culture had no effect on Fraudulent Financial Reporting of Village Funds.